Arguments and icons divergent modes of religiosity - Whitehouse, Harvey (Oxford Univ. Press, 2000)
"Why are some religious rituals intensely stimulating and memorable occasions, while others are habituated and humdrum routines? Why do some religious practices lead to sectarianism and local divisions, while others serve to unify regional and even world-wide followings? The theory of 'modes of religiosity' which Harvey Whitehouse develops in this book answers these and a range of other questions with reference to a set of interconnections between styles of religious transmission, systems of memory, and patterns of political association."--BOOK JACKET.